Exploring undergraduate paramedic students' understanding and experiences of person-centred care while on practice placement. - McAteer, Lorraine; Brown, Donna (Paramedicine, 2024)
Objective: To explore paramedic students' understanding and experience of the perceived facilitators and barriers to implementing person-centred care in urgent and emergency practice-based placement situations. Aim: To explore paramedic students' understanding of this concept and how it may be applied to clinical practice. Methods: A non-probability convenience sample of participants was drawn from a second-year undergraduate Bachelor of Science (Hons) programme in Paramedic Science, at a United Kingdom university. The programme was underpinned by the Person-centred Practice Framework. Undergraduate paramedic students participated in face-to-face, audio-recorded, semi-structured interviews. A qualitative reflexive thematic analysis was then conducted to identify themes arising from the data. Results: Ten participants were interviewed. Four key themes emerged from the data: (1) realising person-centred prerequisites which have two sub-themes – curriculum and reality of practice, (2) challenge of high-acuity calls, (3) developing a rapport with vulnerable people and, (4) factors in the macro environment. Conclusion: Paramedic students witnessed moments of person-centred practice and were enabled to reflect on their learning experiences in positive ways, by working with paramedics/practice educators. However, their person-centred ideals were constantly challenged as students negotiated to work in complex, dynamic situations and in a health system under pressure.